Structural, spectroscopic and computational studies on the monoclinic polymorph (form I) of potassium hydrogen disilicate (KHSi2O5). (June 2014) - Schmidmair, D.; Kahlenberg, V.; Perfler, L.; Többens, D. M.
Abstract: Hydrothermal treatment of quartz with 2 M K2 CO3 solutions at 623 K and 1 kbar resulted in the formation of single crystals of the monoclinic polymorph of potassium hydrogen disilicate (KHSi2 O5 or KSi2 O4 (OH)). Basic crystallographic data of this so-called phase I at room conditions are as follows: space group C 2/ m, a = 14.5895(10) Å, b = 8.2992(3) Å, c = 9.6866(7) Å, β = 122.756(10)°, V = 986.36(10) Å 3, Z = 8. The structure was determined by direct methods and refined to a residual of R(|F|) = 0.0224 for 892 independent observed reflections with I > 2σ( I ). The compound belongs to the group of chain silicates. It is based on crankshaft-like vierer double-chains running parallel to [010]. The H atoms are associated with silanol groups. Hydrogen bonding between neighbouring double-chains results in the formation of ∼5 Å wide slabs. The three crystallographically independent K cations with six to eight O ligands provide linkage (1) between the chains of a single slab or (2) between adjacent slabs. Structural investigations have been supplemented by micro-Raman spectroscopy. The interpretation of the spectroscopic data including the allocation of the bands to certain vibrational species has been aided by DFT calculations.